América Latina: gobernanza y el recurso vital - Sandoval Hernández, Federico (SocietàMutamentoPolitica, 2018)
At present the world socioeconomic system is at a great crossroads, the New World Order is in the decisive offensive to achieve its objectives and it is not known if it will succeed. The military industrial complex, negative accumulation of capital based on the destructive sectors, and the productive only as their sustenance, which implemented the empire, is no longer the key to the extermination of the population, which is the product of a change in strategy generated by the end of the cold war. Here the issue of governance based on current indicators of a Latin American sub-region: Ecuador, Bolivia and Venezuela and the challenges that the other subregion faces Brazil, Argentina, Mexico, Chile, Peru and Paraguay, while the Caribbean is going behind. And in the last part we can see the new vital juncture, water stress in Latin America and its inequalities, despite being a continent with sufficient but predatory water resources. Issues that affect mortality but do not compare with Asia and Africa, culminating with a reflection.